Efficacy of treatment methods for uncontrolled hypertension and its effects on atrial fibrillation: A systematic narrative review - Alodhayani, Abdulaziz A.; Alkhushail, Abdullah; Alhantoushi, Mashhor; Alsaad, Saad M.; Almigbal, Turky H.; Alotaibi, Khalid; Batais, Mohammed A.; Altheaby, Abdulrahman; Al Dalbhi, Sultan; Alghamdi, Yasser (International Journal of Health Sciences, 2019)
Objectives: Uncontrolled hypertension is a main predisposing risk factor leading to chronic atrial fibrillation (AF). Although several treatment methods for patients with HTN and AF were developed in past decades, further investigations of their efficacies are needed. This systematic narrative review presents an overview of studies reporting treatment efficacies in patients with HTN and/or AF. Methods: A narrative-based systematic review was performed using EMBASE, Medline, PubMed, Google Scholar, and the Cochrane Library searching for relevant papers published between October 2008 and October 2018. Out of 4481 studies, only 15 studies could be included following the inclusion criteria. Results: Included studies reported treatment measures, measured outcomes, and efficacies in adult patients with HTN and AF with defined interventions and methodologies. Treatment methods with effective outcomes were administration of hydrochlorothiazide, losartan or atenolol, telmisartan or amlodipine, or general antihypertensive drugs. Treatment methods that showed the most effective outcomes (lowering AF recurrence and improving BP control) were those containing pulmonary vein (or antrum) isolation (PVI/PVAI) (6 studies) and/or in conjunction with renal denervation (RDN)(6 studies). Treatment methods showing the most effective outcomes were PVI/PVAI in conjunction with RDN. Conclusion: The latest evidence shows that PVI (in conjunction with RDN in some instances) was more efficacious among patients suffering from HTN and/or AF.